THE IMPACT OF MUSIC THERAPY ON PSYCHOLOGICAL PROTECTION MECHANISMS AS AN INNOVATIVE APPROACH TO STRENGTHEN CHILDREN'S MENTAL HEALTH IN THE CONDITIONS OF GLOBALIZATION. (Universal International Scientific Journal, 2026)
Music therapy in preschool children is an effective tool for developing psychological defense mechanisms, reducing stress, and increasing emotional stability. Musical activities with parents help strengthen children's mental stability. The thesis highlights the pedagogical and practical significance of music therapy in the context of family psychology.
Keywords: Preschool age, Psychological defense mechanisms, Music therapy, Emotional stability, Family psychology, Stress reduction, Social adaptation.